ANTIBACTERIAL ACTIVITY OF BINAHONG ROOT EXTRACT (Anredera cordifolia (Ten.) Steenis) IN TREATMENT OF BOILS - Pattiwael, Syane; Awan, Ali; Mahulette, Ferymon (Universitas Pattimura, 2022)
Infectious diseases caused by Staphylococcus aureus can be cured with traditional medicine, One example of a plant that has antibacterial power is binahong root. This study aims to determine the minimum inhibitory concentration (MIC) and minimum killing concentration (MBC) of binahong root extract against the growth of Staphylococcus aureus bacteria. Binahong root extract was obtained from maceration using absolute ethanol solvent. Furthermore, the extract obtained was made with a concentration dilution of 5%, 10%, 15% and 20%. The method used is disc diffusion. The results showed that each concentration of binahong root extract had an inhibitory effect on the growth of Staphylococcus aureus bacteria. This is influenced by the active compounds contained in the binahong root extract such as flavonoids, saponins, tannins, and alkaloids. Binahong root extract concentrations of 5%, 10%, 15%, and 20% were found to have zones of inhibition against the growth of S. aureus bacteria and the minimum inhibitory level (MIC) of Binahong root extract against the growth of S. aureus bacteria at a concentration of 5%.